2011
DOI: 10.1128/aac.01801-10
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin Inhibits Expression of the GacA-Dependent Small RNAs RsmY and RsmZ in Pseudomonas aeruginosa

Abstract: Azithromycin at clinically relevant doses does not inhibit planktonic growth of the opportunistic pathogen Pseudomonas aeruginosa but causes markedly reduced formation of biofilms and quorum-sensing-regulated extracellular virulence factors. In the Gac/Rsm signal transduction pathway, which acts upstream of the quorum-sensing machinery in P. aeruginosa, the GacA-dependent untranslated small RNAs RsmY and RsmZ are key regulatory elements. As azithromycin treatment and mutational inactivation of gacA have striki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 49 publications
9
56
2
Order By: Relevance
“…Data from this study and others have shown that rsmYZ transcription requires RsmA (Fig. 4B) (57). We also found that plasmid-expressed RsmA results in a significant increase in expression of the P rsmY-lacZ and P rsmZ-lacZ reporters.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Data from this study and others have shown that rsmYZ transcription requires RsmA (Fig. 4B) (57). We also found that plasmid-expressed RsmA results in a significant increase in expression of the P rsmY-lacZ and P rsmZ-lacZ reporters.…”
Section: Discussionsupporting
confidence: 61%
“…4B) (57). We observed the same using P rsmY-lacZ and P rsmZ-lacZ transcriptional reporters and also saw that plasmid-expressed RsmA results in a significant increase in P rsmY-lacZ and P rsmZ-lacZ reporter activities (Fig.…”
Section: Figsupporting
confidence: 60%
“…Previous works aiming to elucidate QS inhibitory mechanisms have reported that the QS inhibitor azithromycin inhibits the expression of rsmY and rsmZ transcription through the PA0588-PA0584 gene cluster (31). However, our transcriptomic data did not show that iberin affected the expression of the PA0588-PA0584 gene cluster, which suggests that iberin uses a different mechanism from that of azithromycin to inhibit the expression of rsmY and rsmZ.…”
Section: Resultscontrasting
confidence: 53%
“…Two bands hybridized to the rsmY probe, as has been seen previously ( Fig. 5D) (30,38). Little difference was seen between a ΔalgR mutant strain and the wild-type PAO1 (data not shown).…”
Section: Resultsmentioning
confidence: 50%
“…The regulation of rsmZ is more complex than rsmY and includes regulators other than GacA (38,40,41). Primer extension analysis confirmed the location of the transcriptional start site in P. aeruginosa that was predicted from P. fluorescens (Fig.…”
Section: Resultsmentioning
confidence: 53%